“Diversity’s good unless you have a Southern accent, then you’re a hick”: Self-evaluation, linguistic insecurity and symbolic domination in Middle Tennessee - Marc-Philippe Brunet (Anglophonia)
The linguistic variety spoken in the south of the United States (Southern American English, hereafter SAE), is a well-documented field of investigation (Farington et al., 2018; Feagin, 2018; Fridland, 2003, 2008; Labov et al., 2006; Nunnally & Bailey, 2018; Reed, 2014). Due to its geographical and social distribution within the USA, SAE is considered by a large proportion of Americans to be one of the most salient varieties of American English, as well as one which is often regarded by speakers (including SAE speakers) as the most “incorrect” (Hasty, 2018; Preston, 1996, 2015; Preston and Robinson, 2008). As a result, SAE linguistic features are socially diagnostic, in that they are systematically associated with specific socio-demographic groups. Southern speakers typically display a high degree of linguistic insecurity regarding their speech, by virtue of the symbolic domination of the linguistic standard in the USA.The present paper explores how SAE speakers respond to the sentiment of linguistic insecurity in a specific linguistic and social community by analyzing a cohort of respondents’ production of the diphthong /aɪ/, as this linguistic variable of SAE is often regarded as a hallmark feature of Southern phonology (Feagin, 2000; Thomas, 2003). In this context, we draw upon on the notion of symbolic domination, that is a lack of awareness regarding the inherently arbitrary nature of a linguistic standard which leads speakers of less prestigious varieties to judge their own linguistic productions through the prism of dominant criteria (Bourdieu, 2001; Bourdieu & Boltanski, 1975).Our study is based on the results of sociolinguistic fieldwork data from Murfreesboro (Middle Tennessee), which was collected in accordance with the theoretical and methodological framework of the PAC research programme and within the scope of the LVTI-Language, Urban Life, Work, Identity sociophonological project (Durand & Przewozny, 2012; Przewozny et al. 2020). The results of our investigation show high degrees of intra-speaker variation in that respondents are shown to rely on self-correction or hyperdialectalism as antagonistic strategies, which are indicative of the variety’s particular position within the dialect hierarchy that is at hand.